Nuprl Lemma : bdd-diff_functionality
∀x1,x2,y1,y2:ℕ+ ⟶ ℤ.  (bdd-diff(x1;x2) 
⇒ bdd-diff(y1;y2) 
⇒ (bdd-diff(x1;y1) 
⇐⇒ bdd-diff(x2;y2)))
Proof
Definitions occuring in Statement : 
bdd-diff: bdd-diff(f;g)
, 
nat_plus: ℕ+
, 
all: ∀x:A. B[x]
, 
iff: P 
⇐⇒ Q
, 
implies: P 
⇒ Q
, 
function: x:A ⟶ B[x]
, 
int: ℤ
Definitions unfolded in proof : 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
iff: P 
⇐⇒ Q
, 
and: P ∧ Q
, 
equiv_rel: EquivRel(T;x,y.E[x; y])
, 
member: t ∈ T
, 
prop: ℙ
, 
uall: ∀[x:A]. B[x]
, 
rev_implies: P 
⇐ Q
, 
trans: Trans(T;x,y.E[x; y])
, 
guard: {T}
, 
sym: Sym(T;x,y.E[x; y])
Lemmas referenced : 
bdd-diff-equiv, 
bdd-diff_wf, 
nat_plus_wf
Rules used in proof : 
sqequalSubstitution, 
sqequalTransitivity, 
computationStep, 
sqequalReflexivity, 
lambdaFormation, 
independent_pairFormation, 
cut, 
lemma_by_obid, 
sqequalHypSubstitution, 
productElimination, 
thin, 
isectElimination, 
hypothesisEquality, 
hypothesis, 
functionEquality, 
intEquality, 
dependent_functionElimination, 
independent_functionElimination
Latex:
\mforall{}x1,x2,y1,y2:\mBbbN{}\msupplus{}  {}\mrightarrow{}  \mBbbZ{}.    (bdd-diff(x1;x2)  {}\mRightarrow{}  bdd-diff(y1;y2)  {}\mRightarrow{}  (bdd-diff(x1;y1)  \mLeftarrow{}{}\mRightarrow{}  bdd-diff(x2;y2)))
Date html generated:
2016_05_18-AM-06_46_32
Last ObjectModification:
2015_12_28-AM-00_24_51
Theory : reals
Home
Index